(untitled) (Research, Society and Development, 2021)
Microorganisms are a promising source of new molecules and a good alternative in the search for antimicrobials. However, their cultivation conditions can influence both their development and their production of biomolecules. The aim of this work was to evaluate the effect of photoexposure on the antimicrobial activity of eight basidiomycetes. These were grown on malt agar medium, at room temperature, maintained with or without photoexposure for ten days. Extracts were obtained with ethyl acetate, which were tested by the agar diffusion method against the pathogens Escherichia coli CBAM 001, Staphylococcus aureus CBAM 0324 and Candida albicans CFAM 1342. The molecular identification of the basidiomycetes was carried out by amplifying and sequencing the fragment of rDNA. The fungi Pleurotus sp. 474 and Gloeophyllum sp. 1153 inhibited the growth of E. coli CBAM 001, S. aureus CBAM 0324 e C. albicans CFAM 1342. None of these pathogens were inhibited by the fungus Schizophyllum commune 1210. The photoexposure was essential for the fungus Earliella scabrosa 1552 to inhibit the growth of C. albicans, while the absence of photoexposure was essential for the fungus Pleurotus sp. 474 inhibit the growth of S. aureus CBAM 0324 and, the fungi Gloeophyllum sp. 1153, Trametes sp. 1232 and Oudemansiella canarii 1528 inhibit E. coli CBAM 001. These results showed the influence of photoexposure on the production of antimicrobials by basidiomycetes, reinforcing the importance of choosing culture conditions.